A linear cobalt(II) complex with maximal orbital angular momentum from a non-Aufbau ground state - Bunting, Philip C; Atanasov, Mihail; Damgaard-Møller, Emil; Perfetti, Mauro; Crassee, Iris; Orlita, Milan; Overgaard, Jacob; van Slageren, Joris; Neese, Frank; Long, Jeffrey R (Science (American Association for the Advancement of Science), 2018)
Orbital angular momentum is a prerequisite for magnetic anisotropy, although in transition metal complexes it is typically quenched by the ligand field. By reducing the basicity of the carbon donor atoms in a pair of alkyl ligands, we synthesized a cobalt(II) dialkyl complex, Co(C(SiMe ONaph) ) (where Me is methyl and Naph is a naphthyl group), wherein the ligand field is sufficiently weak that interelectron repulsion and spin-orbit coupling play a dominant role in determining the electronic ground state. Assignment of a non-Aufbau (d , d ) (d , d ) (d ) electron configuration is supported by dc magnetic susceptibility data, experimental charge density maps, and ab initio calculations. Variable-field far-infrared spectroscopy and ac magnetic susceptibility measurements further reveal slow magnetic relaxation via a 450-wave number magnetic excited state.